Correlation of hydrogen-bonding propensity and anticancer profile of tetrazole-tethered combretastatin analogues - Jedhe, Ganesh S.; Paul, Debasish; Gonnade, Rajesh G.; Santra, Manas K.; Hamel, Ernest; Tam Luong Nguyen; Sanjayan, Gangadhar J. (Bioorganic & Medicinal Chemistry Letters, 2013)
A series of 1,5-disubstituted tetrazole-tethered combretastatin analogues with extended hydrogen-bond donors at the ortho-positions of the aryl A and B rings were developed and evaluated for their antitubulin and antiproliferative activity. We wanted to test whether intramolecular hydrogen-bonding used as a conformational locking element in these analogues would improve their activity. The correlation of crystal structures with the antitubulin and antiproliferative profiles of the modified analogues suggested that hydrogen-bond-mediated conformational control of the A ring is deleterious to the bioactivity. In contrast, although there was no clear evidence that intramolecular hydrogen bonding to the B ring enhanced activity, we found that increased substitution on the B ring had a positive effect on antitubulin and antiproliferative activity. Among the various analogues synthesized, compounds 5d and 5e, having hydrogen-bonding donor groups at the ortho and meta-positions on the 4-methoxy phenyl B ring, are strong inhibitors of tubulin polymerization and antiproliferative agents having IC50 value in micromolar concentrations. (C) 2013 Elsevier Ltd. All rights reserved.
Keywords: Colchicine; Combretastatin; Crystal; Tetrazole; Tubulin

Photodynamic sensitizers modulate cytoskeleton structural dynamics in neuronal cells - Dubey, Tushar; Chinnathambi, Subashchandrabose (Cytoskeleton, 2021)
The neuronal cytoskeleton plays a crucial role in maintaining cell integrity and functioning of neurons. Cytoskeleton deformities have been reported to be associated with neurodegenerative diseases thus; cytoskeleton can be targeted for therapeutic strategies. The therapeutic application of photosensitive molecule is termed as photodynamic therapy (PDT). PDT has been applied in the field of dermatology, cancer biology, and antimicrobial therapy. PDT induces several changes in cells, which include induction of apoptosis, DNA damage, and induction of inflammatory response. PDT has been also reported to modulate cytoskeleton such as actin dynamics. The in vitro studies suggested that PDT using dyes such as Toluidine Blue and Rose Bengal effectively modulated the actin cytoskeleton, neurite outgrowth, tubulin, and Tau aggregation. In this review, we focused on the effect of photosensitized molecules on various cytoskeleton proteins. We hypothesize that PDT could have potency against Alzheimer's disease and other neurodegenerative disorders.
Keywords: Actin; Alzheimer' cytoskeleton modulation; neuronal cytoskeleton; photodynamic therapy; s disease; Tubulin